Competencias de la docencia universitaria para la sociedad del conocimiento: la visión de tres académicos - Calderón, Rutilia; Martínez, René Noé; Euceda, Armando (Revista UNAH INNOV@, 2016)
UNAH INNOV@ No.2 2013: 36-38